Palliative Surgery for Biliary Drainage in an Unresectable Pancreatic Cancer - Rustam Effendi YS; Imelda Rey; Andrie W; Erina Siregar; M Khadafi; Suhelmi - - (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Pancreatic cancer, known for its rapid progression and poor prognosis, usually presents with obstructive jaundice. Biliary drainage can be achieved by various techniques and approaches, with endoscopic drainage as the preferred method. However, open drainage of the biliary tree is indicated when unresectable tumor is found during resection surgery. This is a case of biliary drainage with a double bypass biliodigestive construction, which could be performed in patients with unresectable cancer in the head of the pancreas presenting with obstructive jaundice and gastric outlet obstruction.